Setting a Discourse Space: Correlational Analysis, Foundational Concepts, and Legally Protected Interests in International Criminal Law - Bergsmo, Morten (2018)
The birth of modern international law was traditionally seen as a practical necessity rather than an intellectual enterprise. Since there is no formal mechanism that could eventually ensure States? compliance with its provisions, it was argued that international law was missing the rational enforcement strategies which are common in domestic normative systems. This pragmatic view, which identified international law as a moral, political or social set of rules considered to be an efficient instrument in the hands of the most powerful nations, did not exactly nourish a consistent philosophical approach to its substance. More related to international politics than to law, international law required higher degrees of normativity in order to improve its reach, increase its utility, and endorse its long-standing purpose of regulating the international community. A higher normative character would be accompaniedby an in crescendo philosophical inquiry into its existence, validity and legality.This first chapter of the volume provides the readers with some theoretical basis for the discussion of the philosophical foundations of international criminal law and presents a survey of the content of the first volume.